Manual of plain digital oral and maxillofacial imaging / Mohd Yusmiaidil Putera Mohd Yusof and Nor Hidayah Reduwan - Putera Mohd Yusof, Mohd Yusmiaidil; Reduwan, Nor Hidayah (UiTM Press, 2024)
Manual of Plain Digital Oral and Maxillofacial Imaging explores the dynamic landscape of radiological imaging within the realm of oral and maxillofacial healthcare. In recent decades, the integration of digital technologies has revolutionised the field, offering clinicians enhanced diagnostic capabilities, improved patient care, and greater efficiency in managing complex oral and maxillofacial conditions.